Roman Law as Pamphlet: Fritz Schulz and the Prinzipien des Römischen Rechts between Cesar and Hitler - Sedano Onofri, Renato (História do Direito, 2022)
The present paper argues that the book Prinzipien des römischen Rechts by Fritz Schulz (1879-1959), first published in 1934, besides being a scholarly piece on Roman law, consists also in a Roman-law-based statement against Nazism. The argument is articulated in three parts, being the first dedicated to understanding the development of the national socialist views on Roman law; the second one deals with the Prinzipien against the background of Nazi legal conceptions, trying to grasp how the structure of the book, as well as some of the word-choices employed by Schulz were not determined exclusively by Roman law scholarship, but also intended to dialogue and ultimately re-signify Nazi misconceptions; the third and last part is dedicated to an overview of the reactions on the Prinzipien, with emphasis to the silence of potential Schulz’s allies. Two main conclusions are stated: a) the framework which allowed the development of the Nazi legal doctrine also contained the elements of Schulz reaction against it; b) Schulz’s expulsion of his career and country creates long-term difficulties concerning the evaluation of his work, ignored for years in Germany, in comparison to others, like Hans Kreller, who could stay and eventually adapt their writings for the circumstances after 1945.